Influence of Potential on the Electrodeposition of Co on Au(111) by In Situ STM and Reflectivity Measurements. Issue 12 (1st January 2016) - Di, N.; Damian, A.; Maroun, F.; Allongue, P.
Abstract : We study the influence of the deposition potential on the electrochemical growth of Co on Au(111) in the thickness range 0–8 atomic layers (ML). In-situ STM observations evidence two growth regimes which depend on the deposition potential: at potentials <−1.2 VMSE, Co grows 2D with the initial formation of biatomic islands which rapidly cover the entire Au surface, followed by layer-by-layer growth; at potentials >−1.20 VMSE, Co grows 3D with the formation of large multilayer islands with flat top. In situ fast STM imaging of the Co dissolution process evidences a remarkable thickness dependence of the dissolution potential. Complementary electrochemical and in situ optical reflectivity characterizations of Co dissolution as a function of the Co thickness suggest that the equilibrium potential Co/Co 2+ on Au is shifted by ∼−30 mV with respect to that measured on Co. This value is discussed in terms of Co-substrate binding energy.